Features of bryoflora in the Ukrainian Forest-Steppe (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Bryoflora in the Ukrainian Forest-Steppe is described. Features of taxonomic and ecological-coenotic structure, types of morphs in connection with main environmental factors (such as light, water supply, substrate, pH) are determined with dividing mosses to ecological-coenotic groups.
Keywords: mosses, forest-steppe zone of Ukraine, taxonomic structure, ecological morph.